2018
DOI: 10.1111/cea.13235
|View full text |Cite
|
Sign up to set email alerts
|

Asian children living in Australia have a different profile of allergy and anaphylaxis than Australian‐born children: A State‐wide survey

Abstract: Patterns of allergy/anaphylaxis risk and their triggers differed according to both ethnicity and country of birth, suggesting a gene-environment factor is in play. The difference in patterns for asthma compared with other atopic diseases is surprising and warrants further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…One cause of the differences in the outcomes between population may be lifestyle and environmental factors associated with Asian and non-Asian populations [21][22][23]. Compared with European and American populations, Asian populations have a relatively healthy diet and a lower prevalence of chronic diseases (e.g., diabetes and coronary heart disease) [21][22][23], which have a substantial impact on the prognosis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…One cause of the differences in the outcomes between population may be lifestyle and environmental factors associated with Asian and non-Asian populations [21][22][23]. Compared with European and American populations, Asian populations have a relatively healthy diet and a lower prevalence of chronic diseases (e.g., diabetes and coronary heart disease) [21][22][23], which have a substantial impact on the prognosis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Up until a few years ago in The United Kingdom, parents had been advised not to introduce peanuts into the diet of their children until they were 3 years of age, interestingly, the Jewish population did not apply this restriction, a circumstance which led to a reduced peanut allergy prevalence. 10,11 Studies in France regarding the growing prevalence of this sensitization have found that ingesting peanuts while pregnant, breastfeeding, and at the age during which a complimentary diet is introduced to nursing infants were the cause of increased peanut allergy prevalence. 12 Within the Asian continent, peanut allergy prevalence is not very common, in Korea, Singapore, and the Philippines, its frequency ranges from 0.4 to 1.1 % among children; 13 conversely, in countries such as The United Kingdom, Canada, The United States of America, and Australia the prevalence is almost twice as high; in fact, western countries have doubled their peanut allergy prevalence in the last two decades.…”
Section: Discussionmentioning
confidence: 99%
“…4 Wang et al 5 have now extended this to look at eczema, asthma, food allergy using school entry health questionnaires. 4 Wang et al 5 have now extended this to look at eczema, asthma, food allergy using school entry health questionnaires.…”
Section: The British Society Of Allergy and Clinical Immunology Annuamentioning
confidence: 99%
“…We have previously heard that Asian children who are born in Australia have higher rates of eczema and nut allergy than those born in Asia. 4 Wang et al 5 have now extended this to look at eczema, asthma, food allergy using school entry health questionnaires. They found that children born in Australia to Asian-born mothers were more likely to have food allergy and eczema but not asthma than non-Asian children ( Figure 2).…”
Section: The British Society Of Allergy and Clinical Immunology Annuamentioning
confidence: 99%